2021
DOI: 10.1111/jre.12961
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal hsa_circ_0003948 expression affects chronic periodontitis development by regulating miR‐144‐3p/NR2F2/PTEN signaling

Abstract: Background and Objective This study aimed to investigate the correlation between chronic periodontitis (CP) and abnormal circular RNA (circRNA) expression and to identify the role of hsa_circ_0003948 in the progression of CP. Methods Next‐generation sequencing was utilized to investigate abnormal expression of circRNA in gingival tissues from CP patients and healthy control subjects. Bioinformatics and luciferase reporting analyses were used to clarify the interactive relationship among circRNA, miRNA, and mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…Among these circRNAs, further validation studies suggested that circSERPINE1 has a negative impact on inflammatory response and oxidative stress by regulating the miR‐378h /RORA axis, while circCTHRC1 suppressed cytokine production via sponging let‐7f‐5p to regulate SOCS6 19,21 . CircMAP3K11 promoted the proliferation and inhibited the apoptosis of hPDLSCs via the miR‐511‐3p/TLR4 axis, and circKDELR2 promoted cell proliferation and inhibited apoptosis in response to LPS via the miR‐144‐3p/NR2F2/PTEN axis 18,23 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these circRNAs, further validation studies suggested that circSERPINE1 has a negative impact on inflammatory response and oxidative stress by regulating the miR‐378h /RORA axis, while circCTHRC1 suppressed cytokine production via sponging let‐7f‐5p to regulate SOCS6 19,21 . CircMAP3K11 promoted the proliferation and inhibited the apoptosis of hPDLSCs via the miR‐511‐3p/TLR4 axis, and circKDELR2 promoted cell proliferation and inhibited apoptosis in response to LPS via the miR‐144‐3p/NR2F2/PTEN axis 18,23 …”
Section: Discussionmentioning
confidence: 99%
“…51 Several circRNAs have been suggested that might exert regulations in hPDLSCs cell viability, proliferation, migration, apoptosis, osteogenic differentiation, inflammatory response, oxidative stress, cytokine production, as well as stemness maintenance, including circSERPINE1, circCTHRC1, circMAP3K11, circKDELR2, circCDK8, and CDR1as. 14,15,[17][18][19][20][21]23 Among these circRNAs, further validation studies suggested that circSERPINE1 has a negative impact on inflammatory response and oxidative stress by regulating the miR-378h /RORA axis, while circCTHRC1 suppressed cytokine production via sponging let-7f-5p to regulate SOCS6. 19,21 CircMAP3K11…”
Section: Function Of Circrnas Identified and Their Potential Targets ...mentioning
confidence: 99%
See 3 more Smart Citations